What’s Sex Got to Do With COVID-19? Gender-Based Differences in the Host Immune Response to Coronaviruses - Gadi, Nirupa; Wu, Samantha C.; Spihlman, Allison P.; Moulton, Vaishali R. (Frontiers in Immunology, 2020)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing the coronavirus disease 2019 (COVID-19) pandemic has ravaged the world, with over 4.5 million cases and over 300,000 deaths worldwide as of May 15th 2020. While the elderly are most severely affected, implicating an age bias, a striking factor in the demographics of this deadly disease is the gender bias, with higher numbers of cases, greater disease severity and higher death rates among men versus women across the lifespan. While pre-existing comorbidities, social, behavioral and lifestyle factors contribute to this bias, biological factors underlying the host immune response are crucial contributors. Women mount stronger immune responses to infections and vaccination, and outlive men. Sex-based biological factors underlying the immune response are therefore important determinants of susceptibility to infections, disease outcomes and mortality. Yet gender is a sorely understudied and often overlooked variable in research related to the immune response and infectious diseases, and largely ignored in drug and vaccine clinical trials. Understanding these factors will not only help better understand the pathogenesis of this disease, but also guide the design of effective therapies and vaccine strategies for gender-based personalized medicine. This review focuses on sex-based differences in genes, sex hormones and microbiome underlying the host immune response and their relevance to infections with a focus on Coronaviruses.